2020
DOI: 10.1161/strokeaha.120.031265
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Complications of COVID-19

Abstract: Background and Purpose: Coronavirus disease 2019 (COVID-19) evolved quickly into a global pandemic with myriad systemic complications, including stroke. We report the largest case series to date of cerebrovascular complications of COVID-19 and compare with stroke patients without infection. Methods: Retrospective case series of COVID-19 patients with imaging-confirmed stroke, treated at 11 hospitals in New York, between March 14 and April 26, 2020. Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
121
2
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 13 publications
7
121
2
10
Order By: Relevance
“…In a retrospective COVID-19 study, patients with leukoencephalopathy or cerebral micro-hemorrhages had higher peak D-dimer levels and peak international normalized ratio, lower Glasgow Coma Scale and nadir platelet count, longer ventilation time, and hospitalization, more severe acute respiratory distress syndrome, and worse functional status on discharge compared with patients who had normal brain MRI findings (47). When comparing COVID-19 patients with non-COVID-19 patients, increased frequency of in-hospital stroke onset was found in the former cohort (48 vs. 5%) (32).…”
Section: Association Between Coronavirus Disease 2019 and Abnormal Nementioning
confidence: 92%
See 1 more Smart Citation
“…In a retrospective COVID-19 study, patients with leukoencephalopathy or cerebral micro-hemorrhages had higher peak D-dimer levels and peak international normalized ratio, lower Glasgow Coma Scale and nadir platelet count, longer ventilation time, and hospitalization, more severe acute respiratory distress syndrome, and worse functional status on discharge compared with patients who had normal brain MRI findings (47). When comparing COVID-19 patients with non-COVID-19 patients, increased frequency of in-hospital stroke onset was found in the former cohort (48 vs. 5%) (32).…”
Section: Association Between Coronavirus Disease 2019 and Abnormal Nementioning
confidence: 92%
“…Small cortical ischemic lesions were revealed by MRI in a COVID-19 patient while neither interstitial lung involvement nor abnormal serum inflammation markers were detected (31). Furthermore, a multicenter retrospective study comparing COVID-19 patients with non-COVID-19 patients from 1 year prior found that infection with COVID-19 was the strongest independent risk factor for stroke, followed by deep vein thrombosis and male sex (32). Micro-hemorrhages are best visualized by SWI, presenting as hypoattenuating foci.…”
Section: Neurovascular Eventmentioning
confidence: 98%
“…3 28-30 Furthermore, three studies have found COVID-19 infection to be an independent risk factor for both acute ischemic stroke and LVO. [31][32][33] The COVID-19 paradox…”
Section: Stroke and Covid-19mentioning
confidence: 99%
“…Stroke is a rare but well-documented complication, with most prevalence estimates varying slightly around 0.8%. 2 It is therefore important to elucidate both those at risk of developing stroke and stratifying those at risk of more severe outcomes when stroke occurs.…”
mentioning
confidence: 99%
“…Could it be due to increased prevalence of COVID-19 in BAME groups? 2 Or are BAME populations at relatively greater risk of severe outcomes, including stroke, after COVID-19? 4 Through curation of our blog, we have noted that many studies of stroke in the context of COVID-19 infection are published each week.…”
mentioning
confidence: 99%